The optimal babel: An economic framework for the analysis of dynamic language rights - Bengt-Arne Wickström (Center for Economic Studies and ifo Institute (CESifo), 2010)
We analyze various normatively determined distributions of language rights in multilingual settings. A general model for the analysis of language rights over time in a model with overlapping generations is set up. This model is then first used to find efficient allocations of rights in the tradition of Wicksell. It is shown that, when rights today influence the status of a language in the future, the naïve static analysis has to be augmented in favor of further-reaching minority rights in order to take into account the dynamic aspect. It is then demonstrated that a traditional welfare-economic analysis generally goes even further in the support of minority rights. If a possible externality on other communities is taken into account, however, these results are reversed in a pure efficiency analysis. If redistribution arguments are taken into account, this provides an effect in the opposite direction again.
Keywords: D61; D62; D63; D69; 330; equivalence principle; minority rights; changeable preferences; dynamic preferences; welfare economics; overlapping generations; Sprachpolitik; Mehrsprachigkeit; Minderheitenpolitik; Overlapping Generations; Wohlfahrtseffekt; Theorie